Testing and modification of two peanut shellers - Pinai Thongsawatwong; Singh, Gajendra; Gee-Clough, D.; Koike, Masayuki; The British Government (Colombo Plan) (Bangkok : Asian Institute of Technology, 1982)
Two peanut shellers, one manual and other power operated were modified to make them easy to operate and improve their performance. The improved manual peanut sheller has a mechanism to adjust the required clearance, and a round tooth shelling bar which increases its capacity. The modified manual peanut sheller, operated by two men had a capacity of 32 kg (seed)/h with about 4.8% breakage and 96% shelling efficiency. For the power operated peanut sheller, a feeding mechanism and a blower were designed. The modified sheller has a capacity of about 175 kg(seed)/h at 145 stroke/min shelling bar speed and 2 cm clearance. The machine has 97% shelling efficiency with 4.7% breakage, 0.2% blower loss and about 98.3% cleaning efficiency. The power consumption was about 2.2 kW. Operating costs of both manual and power operated shellers with various cleaning methods were computed. At present wage level the minimum annual planted areas of peanuts to own a manually operated sheller with a winnowing basket and a winnower are 2. 5 ha (2.0 tons of seeds) and 1.6 ha (1.3 tons of seeds) respectively. The minimum area for the ownership of the modified power operated sheller is about 3.1 ha (2 .5 tons of seeds).
Thesis (M.Eng.) - Asian Institute of Technology, 1982
A thesis submitted in partial fulfilment of the requirement for the degree of Master of Engineering, School of Environment, Resources and Development
Keywords: Peanuts; Farm mechanization